2005
DOI: 10.1016/j.neuroimage.2005.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms involved in error processing: A comparison of errors made with and without awareness

Abstract: Event-related fMRI is a powerful tool for localising psychological functions to specific brain areas. However, the number of events required to produce stable activation maps is a poorly investigated and understood problem. Huettel and McCarthy [Huettel, S.A., McCarthy, G., 2001. The effects of single-trial averaging upon the spatial extent of fMRI activation. NeuroReport 12, 2411 -2416] have shown that the spatial extent of activation increases monotonically with the number of events in an analysis. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
302
10
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 284 publications
(347 citation statements)
references
References 53 publications
28
302
10
1
Order By: Relevance
“…, a result observed previously with this task (Hester et al, 2005). Neither the post-STOP nor post-unaware-error effects differed between users and controls.…”
Section: Respond Inhibitsupporting
confidence: 76%
See 2 more Smart Citations
“…, a result observed previously with this task (Hester et al, 2005). Neither the post-STOP nor post-unaware-error effects differed between users and controls.…”
Section: Respond Inhibitsupporting
confidence: 76%
“…To examine conscious recognition of errors we administered the Error Awareness Task (EAT) (see Figure 1) (Hester et al, 2005), a motor Go/NoGo response inhibition task in which subjects make errors of commission of which they are aware (aware errors), or unaware (unaware errors). The EAT presents a serial stream of single color words in congruent fonts, with the word presented for 900 ms followed by a 600 ms inter-stimulus interval.…”
Section: Behavioral Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Hewig et al, 2011;Navarro-Cebrian & Kayser, 2013;Roger, Benar, Vidal, Hasbroucq, & Burle, 2010;Scheffers & Coles, 2000;Shalgi & Deouell, 2012;Wessel, Danielmeier, Morton, & Ullsperger, 2012), it contradicts the traditional view that ERN is related to implicit but not to explicit error awareness (e.g. Ehlis, Herrmann, Bernhard, & Fallgatter, 2005;Endrass et al, 2005Endrass et al, , 2007Hester, Foxe, Molholm, Shpaner, & Garavana, 2005;Hughes & Yeung, 2011;Nieuwenhuis et al, 2001;O'Connell et al, 2007;Overbeek et al, 2005;Steinhauser & Yeung, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Some studies find similar neural correlated for reported and non-reported errors (Nieuwenhuis et al, 2001;Endrass et al, 2007Endrass et al, , 2012O'Connell et al, 2007;Shalgi et al, 2009;Hester et al, 2005Hester et al, , 2009Klein et al, 2007), whereas other studies find different neural correlates for aware and unaware errors (Steinhauser and Yeung, 2010;Wessel et al, 2011;Shalgi and Deouell, 2012). It must be considered, however, that most of these studies are limited to the cortical electrophysiology of error reactivity -behavioral adjustments have not been considered.…”
mentioning
confidence: 98%